Valve-in-valve transcatheter aortic valve replacement (TAVR) leads to lower device success compared to TAVR in native stenosis - Paukovitsch, Michael; Dilaver, Bartu; Felbel, Dominik; Krohn-Grimberghe, Marvin; Buckert, Dominik; Moerike, Johannes; Schneider, Leonhard Moritz; Liewald, Christian; Rottbauer, Wolfgang; Gonska, Birgid (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDespite the lack of randomized-controlled trials in patients with failed bioprosthetic valves, valve-in-valve transcatheter aortic valve replacement (ViV-TAVR) is increasingly used.MethodsOutcomes of consecutive patients treated with ViV-TAVR (N = 100) at our tertiary heart center between 2014 and 2022 were compared to TAVR (N = 2216) in native valves.ResultsPatients median age was 78.5 years (IQR 70.0–84.0) in ViV-TAVR compared to 81.0 (IQR 77.0–85.0) in patients with native aortic stenosis (p < 0.01) with a similar percentage of females in both groups (42% vs. 49.3%, p = 0.18). The median Society of Thoracic Surgeons score for mortality was significantly higher in patients undergoing ViV-TAVR [5.1% IQR 2.6%–8.6% vs. 3.8% IQR 2.4%–6.3%, p < 0.01]. ViV-TAVR was performed in degenerated surgical bioprostheses in 88% and in degenerated transcatheter bioprostheses in 12%. Stenosis was the main mechanism of bioprosthetic valve failure (70%), whereas severe regurgitation was the leading cause in 30%. The overall rate of device success amounted to 66% in ViV-TAVR, compared to 96.1% in TAVR (p < 0.01) and ViV-TAVR was independently associated with reduced device success (OR: 0.07, 95%CI: 0.045–0.12, p < 0.01) in multivariate regression. While ViV-TAVR decreased peak and mean gradients significantly, in 31% of patients elevated mean gradients (≥20 mmHg) were observed at discharge. Small native prosthesis diameter (<20 mm) was the strongest predictor (OR 3.8, 95%CI: 1.5–9.2, p = 0.01) independently associated with elevated gradients after ViV-TAVR.ConclusionViV-TAVR for treatment of degenerated bioprostheses improves aortic valve function. However, device success is lower compared to TAVR in native aortic valve disease, mainly due to elevated postprocedural mean gradients, especially in small bioprostheses.